2020
DOI: 10.7759/cureus.10271
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Periarticular Multimodal Drug Injection Without NSAIDs in Elderly Patients With Displaced Femoral Neck Fractures Undergoing Bipolar Hemiarthroplasty: A Prospective Triple-Blinded RCT

Abstract: Introduction Recently, periarticular multimodal drug injection (PMDI) has demonstrated the ability to significantly reduce early postoperative pain with hip fractures in the elderly. Nonetheless, data on PMDI without non-steroidal anti-inflammatory drugs (NSAIDs) in these patients are still doubtful. The current study has evaluated the effect of PMDI with NSAIDs in elderly femoral neck fractures (FNFs) underlying bipolar hip arthroplasty (BHA). Materials and methods A prospective triple-blinded randomized cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Our findings of reduced opioid consumption are in accordance with 2 other randomized trials on hemiarthroplasty patients ( 11 , 12 ). These studies also found reduced pain for the LIA group.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings of reduced opioid consumption are in accordance with 2 other randomized trials on hemiarthroplasty patients ( 11 , 12 ). These studies also found reduced pain for the LIA group.…”
Section: Discussionsupporting
confidence: 92%
“…The other study used LIA without NSAIDs ( 12 ). Their findings of reduced pain sensation, however, were after 36 and 60 hours postoperatively, which is quite late when reckoning that the LIA effect would last up to 24 hours ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations